PENGARUH RASIO PROFITABILITAS DAN RASIO SOLVABILITAS TERHADAP PERTUMBUHAN LABA PADA PT ASTRA INTERNASIONAL TBK PERIODE 2013-2023 - Nishadelia Devinka Arisandi; Endang Nurita (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine and analyze the effect of profitability variables and analyze the effect of solvency variables on profit growth. The research method used is a quantitative method and in the form of secondary data, where the data in this study were obtained based on financial reports on the IDX. The results of the Profitability Variable analysis using Return On Asset (ROA) partially have no effect on Profit Growth, because the results obtained are tcount> ttable, namely 2.2697 > 2.262 and a significant value of 0.0529 > 0.05. The Solvency Variable using Debt To Equity Ratio (DER) partially has no effect on Profit Growth, because the results obtained are tcount> ttable, namely -1.880585 < 2.228 and a significant value greater than 0.05 (0.0928 > 0.05). Based on the simultaneous test, it shows that Return On Asset (ROA) and Debt To Equity Ratio (DER) simultaneously have no effect on profit growth. This is evidenced by the value of Fcount < Ftable which is 0.483054 < 4,46 and a significant value of 0.0714 > 0.05.